Adverse impact of marijuana use on clinical outcomes among psychiatry patients with depression and alcohol use disorder. (January 2018) - Bahorik, Amber L.; Campbell, Cynthia I.; Sterling, Stacy A.; Leibowitz, Amy; Travis, Adam; Weisner, Constance M.; Satre, Derek D.
Abstract: This study examined whether marijuana use was associated with clinically problematic outcomes for patients with depression and alcohol use disorder (AUD). The sample consisted of 307 psychiatry outpatients with mild to severe depression and past 30-day hazardous drinking/drug use, who participated in a trial of substance use treatment. Participants were assessed for AUD based on DSM-IV criteria. Measures of marijuana use, depression symptoms, and functional status related to mental health were collected at baseline, 3, and 6 months. Differences in these outcomes were analyzed among patients with and without AUD using growth models, adjusting for treatment effects. Marijuana was examined as both an outcome (patterns of use) and a predictor (impact on depression and functioning). Forty percent used marijuana and about half the sample met AUD criteria. Fewer patients with AUD used marijuana than those without AUD at baseline. Over 6 months, the proportion of patients with AUD using marijuana increased compared to those without AUD. Patients with AUD using marijuana had greater depressive symptoms and worse functioning than those without AUD. These findings indicate that marijuana use is clinically problematic for psychiatry outpatients with depression and AUD. Addressing marijuana in the context of psychiatry treatment may help improve outcomes. Highlights: Patients with depression frequently used marijuana and nearly half met the AUD criteria. Fewer patients with AUD were using marijuana at baseline compared to patients without AUD. Patients with AUD using marijuana increased over 6 months compared to those without AUD. Patients with AUD using marijuana had worse clinical outcomes than patients without AUD. Addressing marijuana use in outpatient psychiatry treatment may help improve outcomes.